A Better Way to Decrease Knee Swelling in Patients with Knee Osteoarthritis: A Single-Blind Randomised Controlled Trial. (2nd May 2019) - Sari, Zübeyir; Aydoğdu, Onur; Demirbüken, İlkşan; Yurdalan, S. Ufuk; Polat, M. Gülden
Abstract : Objective . In this study, we compared the effects of intermittent pneumatic compression along with conventional treatment with cold-pack treatment along with conventional treatment on clinical outcomes in patients with knee osteoarthritis. Methods . Eighty-nine patients with knee osteoarthritis participated in this study. One group received ultrasound, transcutaneous electrical nerve stimulation, electrical stimulation, exercise, and cold packs. The second group received ultrasound, transcutaneous electrical nerve stimulation, electrical stimulation, exercise, and intermittent pneumatic compression. Range of motion, muscle strength, knee swelling, pain intensity, and functional status were measured at baseline and 4th week. Results . We found significant improvements in range of motion, muscle strength, pain intensity, and functional status after the treatment in both groups (p < 0.05 ). When comparing the effects of these two treatment programs, it was observed that the intermittent pneumatic compression treatment group had a better outcome in terms of knee swelling (p = 0.028 ). Conclusions . According to the results, we could report that intermittent pneumatic compression therapy in addition to conventional treatment has significant positive effects on clinical outcomes in patients with knee osteoarthritis. We could also report that intermittent pneumatic compression therapy along with conventional treatment is superior to cold-pack therapy along with conventional treatment in terms of knee swelling in patients with knee osteoarthritis. This trial is registered withNCT03806322 .